Around Evocações, by Cruz e Sousa: Antecedents, circumstances of publishing and early reviews - Simões, Alvaro Santos [UNESP] (Universidade Federal do Rio Grande do Sul, 2020)
This article is based on the collection of news, reviews and articles in the Rio de Janeiro press, from 1890 to 1893 and from 1898 to 1899, about Cruz e Sousa and his literary work. It is intended to address specifically: 1) some of the probable criteria of organization of Evocações, posthumous work brought to light by the efforts of Nestor Vítor and other admirers of the so-called Dante Negro, 2) the peculiar circumstances in which it was produced and distributed to the public and 3) the first critical manifestations regarding this work. This article also seeks to examine the hypothesis that the mentioned circumstances would have singularly affected the initial reception of this symbolist book.
Em torno das Evocações, de Cruz e Sousa: Antecedentes, circunstâncias e reações à publicação
Keywords: Cruz e Sousa; Evocações; Literary criticism; Press; Symbolism